2016
DOI: 10.1177/1362168816679030
|View full text |Cite
|
Sign up to set email alerts
|

The role of input in second language oral ability development in foreign language classrooms: A longitudinal study

Abstract: The current project longitudinally investigated the extent to which first-year Japanese university students developed their second language (L2) oral ability in relation to increased input in foreign language classrooms. Their spontaneous speech was elicited at the beginning, middle and end of one academic year, and then judged by linguistically trained coders for pronunciation, fluency, vocabulary and grammar qualities. According to the statistical analyses, the total amount of input (operationalized as numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 50 publications
3
53
0
1
Order By: Relevance
“…In our preliminary analyses (reported in another venue: Saito & Hanzawa, 2017), we surveyed the extent to which they had practiced L2 English inside and outside classrooms throughout the project (one academic year). Subsequently, we examined how their varied FL experience backgrounds influenced various aspects of their oral performance at T1, T2 and T3, measured through native raters' subjective pronunciation/lexicogrammar judgements.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary analyses (reported in another venue: Saito & Hanzawa, 2017), we surveyed the extent to which they had practiced L2 English inside and outside classrooms throughout the project (one academic year). Subsequently, we examined how their varied FL experience backgrounds influenced various aspects of their oral performance at T1, T2 and T3, measured through native raters' subjective pronunciation/lexicogrammar judgements.…”
Section: Participantsmentioning
confidence: 99%
“…This could be due to a combination of learner-extrinsic (how the participants had practiced the target language prior to the data collection) and learner-intrinsic (the extent to which their different levels of aptitude, motivation and affect promoted or debilitated their SLA) factors, a result whose discussion was beyond the scope of the study, and closely examined in our precursor research (Saito & Hanzawa, 2017).…”
Section: Aptitude Experience and Proficiency Linkmentioning
confidence: 99%
“…To further pursue the predictive power of experience‐related factors for L2 speech learning, however, future studies should adopt a longitudinal design wherein scholars can track participants’ development patterns for a certain period of time in relation to the quantity and quality of instruction (cf. Saito, ; Saito & Hanzawa, ).…”
Section: Conclusion Implications and Future Directionsmentioning
confidence: 99%
“…However, the incidence and degree of foreign language learning success widely varies between individuals as a function of many variables. By using variance‐based analyses, such as correlations or regressions, rather than means‐based comparisons, such as t tests or ANOVAs, previous studies have found the multivariate nature of L2 oral proficiency development in EFL classrooms to be influenced by age (Larson‐Hall, ) and length of learning (Muñoz, ) and by the nature of L2 use inside classrooms (e.g., see Saito & Hanzawa, , for form‐ vs. meaning‐oriented instruction) and outside instruction (e.g., see Muñoz, , for extracurricular activities). Plonsky and Oswald () provided further discussion about the selection of appropriate statistical analyses for examining multivariate data…”
Section: Introductionmentioning
confidence: 99%